Recent status and life history traits of endangered soft‐mouth trout, Salmo obtusirostris in the River Neretva catchment (Bosnia and Herzegovina) as a consequence of river alteration. (22nd August 2018) - Glamuzina, Branko; Stanić‐Koštroman, Svjetlana; Matić‐Skoko, Sanja; Glamuzina, Luka; Muhamedagić, Samir; Rozić, Irena; Weiss, Steven; Pavličević, Jerko
Abstract: Soft‐mouth trout, Salmo obtusirostris has disappeared from most of its historical distribution range in the River Neretva catchment. Remnant groups are highly fragmented and distribution of the species is restricted to only 15% of it's historical area. The most abundant length range of remnant individuals is between 20 and 40 cm; with a significant decrease of the bigger individuals. Age population structure is dominated by younger fish aged 2, 3 and 4 years, however, age class 4 + and 6 + predominated in the lower river part. Specimens older than 8 years were not observed, and estimated fishing mortality (F) was high, particularly in the upper part of the river (0.786). The River Neretva soft‐mouth trout population is under heavy pressure including anthropogenic habitat changes and illegal fishery, leading to disappearance in number of formerly inhabited areas. The Upper and Lower Neretva are the only areas where the species is still abundant. However, the collapse of the number of old individuals increases the risk of extinction of the remaining wild subpopulations.